Mechanical and Physical Properties of Autoclaved Aerated Concrete Reinforced Using Carbon Fibre of Different Lengths - Ilhami Demir; Ozer Sevim*; Mustafa Kagan Ogdu; Orhan Dogan; Sukru Demir (Tehnički Vjesnik, 2021)
In this study, series of tests have been conducted to indicate the mechanical and physical properties (compressive strength, flexural strength, dry density, thermal conductivity and shrinkage) of autoclaved aerated concrete (AAC) reinforced with carbon fibres of different lengths. AG2/350 AAC block specimens without carbon fibre were prepared as a control specimen. The mixtures were prepared by replacing 0.5% weight of cement in the AAC with 4 mm, 6 mm, 12 mm length carbon fibres and these mixtures were poured into moulds and subjected to 58 °C for 4 hours to expand until reaching workable hardness. After preliminary curing, the produced AAC specimens were subjected to 180 °C and pressure of 11 bar for 6 hours in a steam cure until required hardness. The mechanical and physical properties of the reference and the fibre reinforced AAC specimens were determined and compared to each other. As a result, the use of 12 mm fibre reinforcement in AAC gave the best performance in comparison to the other fibre reinforcements of different lengths by increasing compressive strength for 10.63%, flexural strength of 31.48% and thermal conductivity up to 4.23% while reducing the shrinkage ratio to 51.47%. Herein for the specimen using 0.5% replacement of the AAC in weight with 12 mm carbon fibre is recommended.